Coenzyme Q10 Inhibits the Aging of Mesenchymal Stem Cells Induced by D-Galactose through Akt/mTOR Signaling. (18th February 2015) - Zhang, Dayong; Yan, Bingxi; Yu, Shanshan; Zhang, Chong; Wang, Baoming; Wang, Yayan; Wang, Junbo; Yuan, Zhanggen; Zhang, Lihuang; Pan, Jianping
Abstract : Increasing evidences indicate that reactive oxygen species are the main factor promoting stem cell aging. Recent studies have demonstrated that coenzyme Q10 (CoQ10) plays a positive role in organ and cellular aging. However, the potential for CoQ10 to protect stem cell aging has not been fully evaluated, and the mechanisms of cell senescence inhibited by CoQ10 are still poorly understood. Our previous study had indicated that D-galactose (D-gal) can remarkably induce mesenchymal stem cell (MSC) aging through promoting intracellular ROS generation. In this study, we showed that CoQ10 could significantly inhibit MSC aging induced by D-gal. Moreover, in the CoQ10 group, the expression of p-Akt and p-mTOR was clearly reduced compared with that in the D-gal group. However, after Akt activating by CA-Akt plasmid, the senescence-cell number in the CoQ10 group was significantly higher than that in the control group. These results indicated that CoQ10 could inhibit D-gal-induced MSC aging through the Akt/mTOR signaling.